Modelling retailer-based exemptions in flavoured tobacco sales restrictions: national estimates on the impact of product availability. Issue 11 (26th November 2020) - Schillo, Barbara A; Benson, Adam F; Czaplicki, Lauren; Anesetti-Rothermel, Andrew; Kierstead, Elexis C; Simpson, Randall; Phelps, Natasha C; Herman, Peter; Zhao, Chang; Rose, Shyanika W
Abstract : Objectives: More than 250 US localities restrict sales of flavoured tobacco products (FTPs), but comprehensiveness varies, and many include retailer-based exemptions. The purpose of this study is to examine resulting changes in the US retail environment for FTPs if there was a hypothetical national tobacco control policy that would prohibit FTP sales in all retailers except (1) tobacco specialty stores or (2) tobacco specialty stores and alcohol outlets. Design and setting: A cross-sectional analysis of the FTP retail environment in every US Census tract (n=74 133). FTP retailers (n=3 10 090) were enumerated using nine unique codes from a national business directory (n=296 716) and a national vape shop directory (n=13 374). Outcome measures: We assessed FTP availability using static-bandwidth and adaptive-bandwidth kernel density estimation. We then calculated the proportion of FTP stores remaining and the mean density of FTP retailers under each policy scenario for the overall population, as well as across populations vulnerable to FTP use. Results: Exempting tobacco specialty stores alone would leave 25 276 (8.2%) FTP retailers nationwide, while exempting both tobacco specialty stores and alcohol outlets would leave 54 091 (17.4%) retailers. On average, the per cent remaining FTP availability per 100 000 total population was 7.1% for a tobacco specialty store exemption and 18.1% for a tobacco specialty store and alcohol outlet exemption. Overall, density estimate trends for remaining FTP availability among racial/ethnic populations averaged across Census tracts mirrored total population density. However, estimates varied when stratified by metropolitan status. Compared with the national average, FTP availability would remain 47%–49% higher for all racial/ethnic groups in large metropolitan areas. Conclusions: Retailer-based exemptions allow greater FTP availability compared with comprehensive policies which would reduce FTP availability to zero. Strong public policies have the greatest potential impact on reducing FTP availability, particularly among urban, and racial/ethnic minority populations.